Significance of Circulating and Crevicular Matrix Metalloproteinase-9 in Rheumatoid Arthritis-Chronic Periodontitis Association - Isabela Silosi; Manole Cojocaru; Lili Foia; Mihail Virgil Boldeanu; Florin Petrescu; Petra Surlin; Viorel Biciusca (Journal of Immunology Research)
In the recent years, statistically significant associations between rheumatoid arthritis (RA) and periodontal disease have been identified. Emerging as a chronic inflammatory joint disease, RA displays various features and pathogenetic events similar to chronic periodontitis (CP). The purpose of this study was to evaluate the utility of determining systemic and crevicular levels of metalloproteinase-9 (MMP-9) as potential biomarkers for association between RA and CP. A total of fifty-six patients were included in the study. The subjects were categorized into four groups as follows: healthy-control (n=21), active RA (n=16), CP (n=14), and RA-CP association (n=12). Assessment of serum and crevicular concentrations of total MMP-9 (active and pro-MMP-9) was based on ELISA technique. The results of this study showed statistically significant differences of serum MMP-9 between patients groups and control. Serum levels of MMP-9 were similar in RA and RA-CP associated patients. Gingival crevicular fluid (GCF) recorded increased MMP-9 levels in RA-CP association subjects as compared to CP. Considering that RA-CP association is characterized by a disregulation of the inflammatory response, MMP-9 may play a role in the pathogenesis of RA-CP association. MMP-9 is therefore a sensitive tool in the diagnosis and management of patients affected by this binomial association.